Analysis of the Case Law Under Art 85 and 86 Of PDPL - Radev, Stefan (Research Papers, 2025)
The article examines the accumulated case law related to the challenge of penal decrees issued in connection with the violations provided for in Chapter Nine of the PDPA. An assumption is made regarding the scarce case law, linking it to the regulation of the agreement under the ZANN and the provisions of Articles 85 and 86 of the PDPA are compared and analyzed. Attention is drawn to the late revision of the PDPA as an argument for the lack of accumulation of case law.